Dynamics of Muslim Millennials in Charity Donation: A Donor-Side Perspective - Firdan Thoriq Faza; Astiwi Indriani (Jurnal Ekonomi Syariah Teori dan Terapan, 2022)
ABSTRAK Penelitian ini bertujuan untuk mengeksplorasi bagaimana pengalaman donasi para donatur milenial muslim, dengan fokus utama untuk mengetahui rasionalitas donatur konsumen yang mendasari pengalaman donasi. Metode Interpretative Phenomenological Analysis (IPA) dilakukan untuk menggambarkan dinamika milenial muslim dalam memulai berdonasi, mengembangkan niat, dan mengidentifikasi alternatif penyaluran donasi. Sepuluh peserta dipilih dari Semarang, Jawa Tengah, Indonesia, menggunakan purposive-sampling dengan kriteria dan persyaratan yang telah ditentukan untuk memilih partisipan. Data wawancara dianalisis dengan menggunakan teknik deskriptif kualitatif tipe naratif. Hasil penelitian menunjukkan bahwa altruisme dan spiritualitas mendorong pemberian sumbangan. Donatur tidak mengharapkan adanya timbal balik dari penerima, pemahaman ini kemudian dimaknai sebagai altruisme. Dari perspektif agama, donasi merupakan bentuk ketaatan kepada Tuhan dengan menjalankan apa yang diperintahkan dan hanya mengharapkan balasan-Nya. Semua partisipan adalah pemeluk agama Islam, sehingga motivasi berdasarkan nilai-nilai spiritual hanya terbatas pada keyakinan satu agama dan secara umum tidak dapat mewakili banyak keyakinan. Temuan selanjutnya, ada transformasi donasi dari donasi langsung, ke lembaga donor dan yang terbaru melalui teknologi digital yang bisa menjadi fokus penelitian di masa depan. Kata Kunci: Altruisme, Perilaku Donasi, Donatur Milenial, Interpretative Phenomenology Analysis. ABSTRACT This study explores the donation experience of Muslim millennial donors, with the main focus on discovering the consumer donor rationality underlying donation experience. The Interpretative Phenomenological Analysis (IPA) method was conducted to depict the dynamics of Muslim millennials in starting a money donation, developing intention, and identifying the alternative distribution for donations. Ten participants were chosen from Semarang, Central Java, Indonesia, using purposive sampling with predetermined criteria and requirements for selecting participants. The interview data were then analyzed using a narrative type of descriptive qualitative technique. The research results show that altruism and spirituality encourage donation-making. Donors do not expect any reciprocity from the recipient; this understanding is interpreted as altruism. From a religious perspective, this is a form of the donor's obedience to God by carrying out what was ordered and only expecting the reward. All participants are adherents of Islam, so motivation based on spiritual values only focuses on the beliefs of one religion and cannot generally represent many beliefs. Further findings show a transformation of donations from direct donations to donor agencies and, most recently, through digital technology, focusing on future research. Keywords: Altruism, Donation Behavior, Millennial Donor, Interpretative Phenomenology Analysis.   REFERENCES Anik, L., Aknin, L. B., Norton, M. I., & Dunn, E. W. (2009). Feeling good about giving: The benefits (and costs) of self-interested charitable behavior. Harvard Business School Marketing Unit Working Paper, 10-012. http://dx.doi.org/10.2139/ssrn.1444831 Aufa S, F. N. (2018). Faktor-faktor yang mempengaruhi keputusan donatur dalam menyalurkan infaq via social networking site (SNS) (Studi pada masyarakat kota Malang). Jurnal Ilmiah Mahasiswa FEB Universitas Brawijaya, 7(1), 1-11. Bjalkebring, P., Västfjäll, D., Dickert, S., & Slovic, P. (2016). Greater emotional gain from giving in older adults: Age-related positivity bias in charitable giving. Frontiers in Psychology, 7, 1-8. https://doi.org/10.3389/fpsyg.2016.00846 Charities Aid Foundation. (2021). CAF world giving index 2021: A global pandemic special report. Retrieved from https://www.cafonline.org/docs/default-source/about-us-research/cafworldgivingindex2021_report_web2_100621.pdf Choy, K., & Schlagwein, D. (2016). Crowdsourcing for a better world: On the relation between IT affordances and donor motivations in charitable crowdfunding. Information Technology & People, 29(1), 1-33. http://dx.doi.org/10.1108/ITP-09-2014-0215 Eveland, V. B., & Crutchfield, T. N. (2007). Understanding why people do not give: Strategic funding concerns for aids-related nonprofits. International Journal of Nonprofit and Voluntary Sector Marketing, 12(1), 1–12. https://doi.org/10.1002/nvsm.7 Hua, X., Huang, Y., & Zheng, Y. (2019). Current practices, new insights, and emerging trends of financial technologies. Industrial Management & Data Systems, 119(7), 1401-1410. https://doi.org/10.1108/IMDS-08-2019-0431 Kashif, M., Jamal, K. F., & Rehman, M. A. (2018). The dynamics of zakat donation experience among Muslims: A Phenomenological Inquiry. Journal of Islamic Accounting and Business Research, 9(1), 45-58. https://doi.org/10.1108/JIABR-01-2016-0006 La Kahija, Y. F. (2017). Penelitian fenomenologis jalan memahami pengalaman hidup. Yogyakarta: Kanisius. Liu, L., Suh, A., & Wagner, C. (2018). Empathy or perceived credibility? An empirical study on individual donation behavior in charitable crowdfunding. Internet Research, 28(3), 623-651. https://doi.org/10.1108/IntR-06-2017-0240 Mustafa, M. O. A., Mohamad, M. H. S., & Adnan, M. A. (2013). Antecedents of zakat prayers’ trust in an emerging zakat sector: An exploratory study. Journal of Islamic Accounting and Business Research, 4(1), 4-25. https://doi.org/10.1108/17590811311314267 Muzikante, I., & Skuskovnika, D. (2018). Human value and atitudes towards money. Society, Integration, Education, 7, 174-183. http://dx.doi.org/10.17l770/sie2018vol7.3433 Neumayr, M., & Handy, F. (2017). Charitable giving: What influences donors’ choice among different causes? Voluntas: International Journal of Voluntary and Nonprofit Organizations, 30, 783-799. https://doi.org/10.1007/s11266-017-9843-3 Opoku, R.A. (2013). Examining the motivational factors behind charitable giving among young people in a prominent Islamic country. International Journal of Nonprofit and Voluntary Sector Marketing, 18(3), 172-186. https://doi.org/10.1002/nvsm.1457 Otto, P. E., & Bolle, F. (2011). Multiple facets of altruism and their influence on blood donation. Jurnal Sosio-Economics, 40(5), 558-563.  https://doi.org/10.1016/j.socec.2011.04.010 Saksa, J. (2015). An investigation of research on altruism in recent literature of the three sectors: Public, private, and non-profit. Honors Projects, 556, 1-27. Retrieved from https://scholarworks.gvsu.edu/ honorsprojects/556 Shabbir, H., Palihawadana, D., & Thwaites, D. (2007). Determining the antecedents and consequences of donor-perceived relationship quality: A dimensional qualitative research approach. Psychology and Marketing, 24(3), 271-293. https://doi.org/10.1002/mar.20161 Smith, R. W., Faro, D., & Burson, K. A. (2013). More for the many: The influence of entitavity on charitable giving. Journal of Consumer Research, 39(5), 961-976. https://doi.org/ 10.1086/666470 Stebbins, E., & Hartman, R. L. (2013). Charity brand personality: Can smaller charitable organizations leverage their brand's personality to influence giving. International Journal of Nonprofit and Voluntary Sector Marketing, 18(3), 203-215. https://doi.org/ 10.1002/nvsm.1468 Teah, M., Lwin, M., & Cheah, I. (2014). Moderating role of religious beliefs on attitudes towards charities and motivation to donate. Asia Pacific Journal of Marketing and Logistics, 26(5), 738-760. https://doi.org/10.1108/APJML-09-2014-0141 Weng, Q., & He, H. (2019). Geographic distance, income and charitable giving: Evidence from China. The Singapore Economic Review, 64(5), 1145-1169. https://doi.org/10.1142/ S0217590818500212 Wiepking,  P., & James III, R. N. (2013). Why are the oldest old less generous? Explanations for the unexpected age-related drop in charitable giving. Ageing and Society, 33, 486-510. https://doi.org/10.1017/S0144686X12000062 Yardley, L. (2007). Demonstrating validity in qualitative psychology. InJ. A. Smith (Eds.), Qualitative psychology: A practical guide to research methods (pp. 235-251). London: Sage.